Prognostic Markers in Patients with Cirrhosis and Portal Hypertension Who Have Not Bled. Issue 3 (27th May 2013) - Poca, Maria; Puente, Angela; Graupera, Isabel; Villanueva, Càndid
Abstract : Prognostic markers of compensated cirrhosis should mainly investigate factors involved with progression to decompensation because death in cirrhosis is related with decompensation. Portal hypertension plays a crucial role in the pathophysiology of most complications of cirrhosis. Accordingly, HVPGmonitoring has strong prognostic value. An HVPG ≥ 10 mmHg determines a significantly higher risk of developing decompensation. Esophageal varices also can develop when the HVPG is ≥ 10 mmHg, although an HVPG ≥ 12 mmHg is required for variceal bleeding to occur. Monitoring the changes induced by the treatment of portal hypertension on HVPG, provides strong prognostic information. In compensated cirrhosis hemodynamic response is appropriate when the HVPG decreased to <10 mmHg or by > 10% from baseline, because the incidence of complications such as bleeding or ascites significantly decrease when these targets are achieved. Whether serum markers, such as the FibroTest, they, may be valuable to predict decompensation should be established. Transient Elastography is a promising technique that has shown an excellent accuracy to detect severe portal hypertension. However, whether it can adequately determine clinically significant portal hypertension, and risk of developing varices and decompensation, should be established. Magnetic Resonance Elastography is also promising.